Eristalis (Eristalis) tenax Linnaeus 1758 - El-Hawagry, Magdi S.; Gilbert, Francis (Zenodo, 2019)
Eristalis ( Eristalis ) tenax Linnaeus, 1758 Musca tenax Linnaeus, 1758: 591. Type locality: Sweden. Conops vulgaris Scopoli, 1763: 354. Type locality: Slovenia. Musca porcina De Geer, 1776: 98. Unjustified new name of tenax. Musca apiformis Geoffroy, 1785: 488. Type locality: Sweden. Eristalis campestris Meigen, 1822: 387. Type locality: Germany & Austria. Eristalis hortorum Meigen, 1822: 387. Type locality: Germany. Eristalis sylvaticus Meigen, 1822: 388. Type locality: Austria. Eristalis vulpinus Meigen, 1822: 388. Type locality: Austria. Eristalis cognatus Wiedemann, 1824: 37. Type locality: India (Tranquebar). Eristalis sinensis Wiedemann, 1824: 37. Type locality: China. Eristalis nili Rondani, 1850: 166. Type locality: Egypt. Eristalis columbica Macquart, 1855: 108. Type locality: Colombia. Eristalis ventralis Thomson, 1869: 489. Type locality: China. Eristalis tenax var. alpinus Strobl, 1893: 185. Type locality: Austria. Eristalis claripes Abréu, 1924: 104. Type locality: Canary Is. Material examined : 1 male, Arish, 6.V.1934, leg. Shafik; 1 female, Ismailia, 7.IV.1926, leg. Tewfik; 1 female, Wadi Rishrash, 21.VI.1932, leg. Tewfik; [EFC]. World distribution : Cosmopolitan, known from all regions except the Antarctic. Egyptian localities : Coastal Strip: Alexandria, Mariout. Eastern Desert: Ismailiya, Wadi Hoff, Wadi Rishrash. Fayoum: Fayoum City, Kom Osheem. Lower Nile Valley & Delta: Cairo, El-Gebel El-Asfar, El-Marg, Embaba, Ezbet El-Nakhl, Kombira, Shubra. Sinai: El-Arish. [Sources: Efflatoun 1922, Shaumar & Kamal 1978 and the examined museum material]. Activity period in Egypt : Throughout the year. Remarks : E. tenax is the most widely distributed syrphid in Egypt (Efflatoun 1922). Adults fly up to 5m from ground, spending a considerable amount of time resting on flowers and foliage, and in the evenings can be found sunning on the foliage of bushes and shrubs (Speight 2017). A wide range of flowers is visited by this species, including white, yellow, pink and blue blooms (De Buck, 1990). ...